Flexibility - Chod, Jiri (Henry Stewart Talks, 2012)
Resource flexibility, Risk pooling, Revenue maximization, Operational Hedging, Network flexibility, Inventory centralization, Inventory transshipment, Delayed product differentiation, Component commonality, Mass customization, Make-to-order and service operations, Volume flexibility, Flexibility and lean operations, Flexibility and global operations